Pro-Ecological Energy Solutions which Minimize The Use of Fossil Fuels in The Roofed Facilities (Agricultural Engineering, 2017)
The paper, based on the materials of the Main Statistical Office, presents a present state of use of renewable energy sources in the Polish power industry. Moreover, based on the available data, the amount of energy used for roofed production was estimated (heat, electric energy). Additionally, the amount of emission to atmosphere of hazardous substances (sulphur oxides, lead oxides, carbon dioxide and carbon oxide, dust and benzo(a) piren) was determined. Based on the available literature, technical solutions, which are analysed in various scientific centres, which aim at decrease of fuel consumption, were presented. A detailed analysis focused on the possibility of substituting fossil fuel with another heat source, effectiveness of energy use, increase of insulation ability of the facility roof and modification of greenhouses structures. From among the available energy sources, problems and its possible use in horticultural production were presented. The following energy sources were analysed: geothermal energy, sun and wind energy, biomass, heat pump; co-generative system (triple co-generative). Also barriers and possibilities of use of own boiler house and heat from central heating grid as energy source were analysed.